The Athlete's guide to making weight - Macedonio, Michele A. 4 0 16; Dunford, Marie; 5 (Champaign, IL : Human Kinetics, 2009)
Offers advice to athletes on how to obtain the optimal competitive weight for their sport based on analyses of top athletes, competitive trends, and positional demands in twenty-one sports, and includes discussion of body composition, nutritional requirements, and training programs, as well as customizable meal plans.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Physiological aspects.;Nutrition.;Regulation.;Physiological aspects.;Nutrition. -- Sports;Athletes;Body weight;Sports medicine.;Sports;Athletes;Body weight.;Sports medicine; 20; 2